2008
DOI: 10.1080/13825580701336882
|View full text |Cite
|
Sign up to set email alerts
|

Aging and Inhibition of a Prepotent Motor Response during an Ongoing Action

Abstract: Inhibitory functions are key mechanisms underlying age related decline (Park & Gutchess, 2000, in: Cognitive aging: A primer. Hove: Psychology Press), yet few studies have investigated their impact on everyday tasks involving action as well as cognition. Using an everyday-based go/no-go task we devised a motor analogy of traditional neuropsychological tests to investigate in 134 older (aged 60-88) and 133 younger adults (aged 20-59) the ability to inhibit a prepotent motor response during an ongoing action. Ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 58 publications
2
22
0
Order By: Relevance
“…This Wnding was extended in a very recent study (Potter and Grealy 2007) using a go/no-go task, again showing that older subjects produced more inhibition failures. Kramer et al (1994) also found that elderly compared to younger adults, were less able to inhibit overt responses: when both elderly and young adults were asked to perform a series of tasks measuring inhibitory functions, it was found that older adults had more diYculty than younger ones in stopping the overt response and adopting new rules, indicating that aging decreases the ability to inhibit an overt response in favour of an intentional response.…”
Section: Introductionmentioning
confidence: 88%
“…This Wnding was extended in a very recent study (Potter and Grealy 2007) using a go/no-go task, again showing that older subjects produced more inhibition failures. Kramer et al (1994) also found that elderly compared to younger adults, were less able to inhibit overt responses: when both elderly and young adults were asked to perform a series of tasks measuring inhibitory functions, it was found that older adults had more diYculty than younger ones in stopping the overt response and adopting new rules, indicating that aging decreases the ability to inhibit an overt response in favour of an intentional response.…”
Section: Introductionmentioning
confidence: 88%
“…Stair descent was particularly demanding on knee extensors and participants were clearly at their functional capacity descending stairs. A parallel study of these participants showed that they also made errors when changing from one motor task to another [22] for example, during the transition from exiting the stairs and proceeding to walk on level surface. Although we did not investigate this aspect of the functional task in this study, it is safe to assume that the forces and moments generated during this phase will increase as the subject changes direction.…”
Section: Functional Demand During Sa and Sdmentioning
confidence: 96%
“…For example, studies have revealed age-related deficits in restraining a response (Kok, 1999; May and Hasher, 1998) and ignoring/suppressing visually distracting information (Alain and Woods, 1999; Chao and Knight, 1997; Clapp and Gazzaley, 2010; Gazzaley et al, 2008; Gazzaley et al, 2005; West and Alain, 2000; Zanto et al, 2010a; Zanto et al, 2010b). More specifically, older adults show diminished response inhibition when required to modify an executed plan of action (Andres et al, 2008; Bedard et al, 2002; Kramer et al, 1994; Potter and Grealy, 2008), as well as visual suppression deficits in the presence of distracting information (Clapp and Gazzaley, 2010; Gazzaley et al, 2008; Hasher et al, 1999). …”
Section: Introductionmentioning
confidence: 99%